Rapid diagnosis of tuberculosis by identification of Antigen 85 in mycobacterial culture system - Ponrut Phunpae (2018)
The standard culture for identification of Mycobacterium tuberculosis takes a long time to perform. We introduce here a method for fast identification of M. tuberculosis in mycobacterial culture system. Antibodies to Antigen (Ag) 85 of M. tuberculosis were produced and subsequently used to develop enzyme-linked immunosorbent assay (ELISA) for detecting Ag85 in the culture filtrate. By this detection, rapid tuberculosis (TB) diagnosis was achieved in comparison to the standard culture system with 89.6% sensitivity and 94% specificity. We thus suggest a new TB diagnosis strategy in which clinical samples are cultured in mycobacteria liquid culture medium. The culture filtrates are taken for detection of the Ag85 by ELISA. Using this strategy, 25%, 50%, 80%, and 90% of TB patients will be detected within day 3, week 1, 2, and 4, respectively. The established assay will enable a faster diagnosis of TB, leading to more efficient treatment of TB patients and control of disease transmission. © 2014 Elsevier Inc.